Application of The Jigsaw Method in Learning Islamic Religious Education at SMAN 1 Sumberasih - Akhmad Lutfi; M. Rohul Ulum; Nazahah Ulin Nuha (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The application of the Jigsaw Method in Islamic Religious Education (PAI) Learning at SMAN 1 Sumberasih is an innovation to empower the learning process. This method aims to encourage student cooperation, develop social skills, and deepen understanding of PAI material. The teacher divides students into small groups with the task of studying certain parts of the material, such as the pillars of prayer, prayer procedures, and the importance of prayer in Islam. Students become experts in the part studied and rejoin a new group consisting of members from each original group. In this new group, they share knowledge, encourage collaboration, and learn from each other. Basically the Jigsaw Method involves dividing learning material into small parts which are then given to groups of students. Each group will be responsible for studying a specific section of the material. After understanding the material well, each group member will return to their original group and teach the part they have learned to other group members. PAI learning using the Jigsaw method does not only focus on mastering the material, but also develops social aspects and skills that are important in everyday life. . This creates a dynamic learning atmosphere, motivates students to be actively involved, and increases their understanding of Islamic teachings and their application in everyday life.